Estimating the Life Course of Influenza A(H3N2) Antibody Responses from Cross-Sectional Data - Kucharski, Adam J.; Lessler, Justin; Read, Jonathan M.; Zhu, Huachen; Jiang, Chao Qiang; Guan, Yi; Cummings, Derek A. T.; Riley, Steven (PLOS Biology, 2015)
A combination of cross-sectional serological data from Southern China and mathematical modeling reveals key aspects of the human immune system's response to seasonal influenza infection.